2022
DOI: 10.1002/anie.202114614
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Epothilone‐Based Microtubule Stabilisers Allow GFP‐Imaging‐Compatible, Optical Control over the Microtubule Cytoskeleton**

Abstract: Optical methods to modulate microtubule dynamics show promise for reaching the micron‐ and millisecond‐scale resolution needed to decrypt the roles of the cytoskeleton in biology. However, optical microtubule stabilisers are under‐developed. We introduce “STEpos” as GFP‐orthogonal, light‐responsive epothilone‐based microtubule stabilisers. They use a novel styrylthiazole photoswitch in a design to modulate hydrogen‐bonding and steric effects that control epothilone potency. STEpos photocontrol microtubule dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Styrylthiazoles as in 8 have not yet been studied as scaffolds for photopharmaceuticals. 16 We were pleased that its isomers' spectra were only ca. 25 nm blue-shifted compared to the SBTs (giving less efficient isomerization at 405 nm), and all other properties, such as its completeness of E → Z photoswitching, were similar to the SBTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Styrylthiazoles as in 8 have not yet been studied as scaffolds for photopharmaceuticals. 16 We were pleased that its isomers' spectra were only ca. 25 nm blue-shifted compared to the SBTs (giving less efficient isomerization at 405 nm), and all other properties, such as its completeness of E → Z photoswitching, were similar to the SBTs.…”
Section: Resultsmentioning
confidence: 99%
“…Photouncaging approaches have been known for some decades; while more recently, photoisomerization-based drug analogues or “photopharmaceuticals” have been developed, to elegantly avoid many of the drawbacks that limited the in vivo use of typical photouncaging methods, such as toxic and/or phototoxic byproducts, requirements for <360 nm wavelengths and high light intensities, slow post-illumination fragmentation, irreversibly photosensitive stock solutions, and non-optical drug release mechanisms (e.g., enzymatic hydrolysis of cages). In the MT field, recent photoswitchable analogues of taxane, epothilone, and colchicinoid , MT inhibitors have all been applied to cellular studies. These photopharmaceuticals have enabled noninvasive, reversible optical control over MT dynamics and MT-associated downstream effects, with cell-specific spatial precision and subsecond-scale temporal precision, and have been brought to bear on research in embryology, neuroscience, and cytoskeleton …”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the anticipation, the resulting compound proved to be unsuitable due to its poor solubility combined with a very low potency and dynamic range of bioactivity photomodulation. Gao et al reasoned that the taxanes’ intrinsic characteristics—including the high molecular weight and low solubility—limit its applicability in the development of photoswitchable analogues [ 50 ].…”
Section: Photoswitchable Microtubule-targeting Agentsmentioning
confidence: 99%
“…Additionally, at high concentrations, the formation of microtubule bundles was observed. Furthermore, the authors demonstrated that STEpo2 enables in situ suppression of microtubule dynamics upon 405 nm pulsing during continuous imaging of GFP-labelled cells using the 487 nm laser [ 50 ].…”
Section: Photoswitchable Microtubule-targeting Agentsmentioning
confidence: 99%
“…10,11 Gaining spatiotemporal control of the stability and structures of MTs using external stimuli is a promising strategy to manipulate specific cell populations with reduced side effects. [12][13][14][15][16][17][18][19] For example, Thorn-Seshold et al have developed Taxol-azobenzene conjugates that allow control of the structures of intracellular MTs by photoisomerization of the azobenzene moiety. 15 Although photoisomerization is useful for modulating the stabilization of MTs, its reversible property might result in moderate MT stabilization.…”
mentioning
confidence: 99%